Mobile based peer feedback in EFL speaking: learners’ motivation, behavioral engagement in feedback provision, and achievement - Yan Ding; Jing Zhu (Asian-Pacific Journal of Second and Foreign Language Education)
Abstract Despite its feasibility and potential, technology-supported peer feedback in foreign language speaking classrooms has been under-researched. The present study aimed to extend this line of research by modeling Chinese postgraduates’ and undergraduates’ motivation, behavioral engagement in feedback provision, and achievement in a particular type of technology-supported peer feedback, i.e., group peer feedback via WeChat in EFL speaking classrooms. The results indicated that the two motivational constructs investigated in the study, namely, expectancy for success and subjective task value did not predict learners’ behavioral engagement in feedback provision; behavioral engagement in feedback provision significantly predicted the assessors’ achievement; and educational level did not moderate the relations between motivation, behavioral engagement in feedback provision, and achievement. The results pointed to the complexity of the relations between motivation and engagement in complicated contexts like technology-supported peer feedback. They also highlighted the value of mobile based group peer feedback tasks in EFL speaking classrooms. Theoretical and pedagogical implications were discussed.